Policy uncertainty and foreign direct investment: Evidence from the China-Japan island dispute - Cheng Chen; Tatsuro Senga; Chang Sun; Hongyong Zhang (Queen Mary University of London, School of Economics and Finance, 2016)
Can a temporary negative shock generate long-lasting effects on economic activities? To show causal evidence, we utilize data from Japanese multinational corporations (MNCs) and explore the economic impact of the unexpected escalation of an island dispute between China and Japan in 2012. Our difference-in-differences (DID) estimation substantiates that a sharp, but temporary fall in local sales of Japanese MNCs in China led to persistent downward deviation of foreign direct investment (FDI) from its trend. Moreover, despite the quick recovery of local sales, Japanese MNCs in China have continued to underestimate their local sales, which generates pessimistic and more dispersed forecast errors after the island crisis. We view this as evidence for a belief-driven channel through which a large and unexpected negative shock leads agents to revise their beliefs and start tail risk hedging.
Keywords: D84; E22; E32; F23; 330; Uncertainty; Forecasts; FDI; Geopolitical Conflicts; Business Cycles